La política exterior de México hacia Sudamérica, 1900-1910 - Pérez Reyes, Elda (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
The Mexican foreign policy toward South America during the last decade of Porfirio Díaz government was not univoca, it contained different rhythms and different interests. Certainly, neither the same one that was assumed in front of United States was because like one knows the conditions they were others. The posture of the operators of the Mexican diplomacy was guided by the position of Mexico in front of the represented nation, for the pursued objectives and the context of the moment. Indeed, the chancellery under the direction of Ignacio Marshal impelled spread initiatives to build a politico-economic alliance with South America, with the purpose of creating a counterbalance to the North American growing interests. In this investigation that has the objective of analyzing the Mexican foreign policy toward South America during the first decade of the XX century, the interest of that régime is exemplified to project a stable vision and moderna2 of Mexico toward the southern region of America.

La política exterior mexicana hacia Sudamérica durante la última década del gobierno de Porfirio Díaz no fue univoca, encerró distintos ritmos y diferentes intereses. Ciertamente, tampoco fue la misma que se asumió frente a Estados Unidos porque como se sabe las condiciones eran otras. La postura de los operadores de la diplomacia mexicana se guió por la posición de México frente a la nación representada, por los objetivos perseguidos y el contexto del momento. En efecto, la cancillería bajo la dirección de Ignacio Mariscal impulsó iniciativas tendientes a construir una alianza político-económica con Sudamérica, con la finalidad de crear un contrapeso a los crecientes intereses norteamericanos. En esta investigación, que tiene el objetivo de analizar la política exterior mexicana hacia Sudamérica durante la primera década del siglo XX, se ejemplifica el interés de ese régimen por proyectar una visión estable y moderna2 de México hacia la región austral de América.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2011-0004; Política exterior; México; Sudamérica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2087